Fear of cancer recurrence in Non- and Hodgkin lymphoma survivors during their first three years of survivorship among French patients. Issue 7 (9th August 2019) - Walburg, V.; Rueter, M.; Lamy, S.; Compaci, G.; Lapeyre-Mestre, M.; Laurent, G.; Despas, F.
ABSTRACT: The aim of this study was to measure the prevalence of FCR among a sample of French lymphoma survivors and to determine factors associated with clinical levels of FCR. The study was conducted with two cross-sectional measures: sociodemographic and anxiety, depression as well as health-related quality of life (HRQoL) scores were measured at the baseline of the post-cancer period and FCR was evaluated during the first 3 years of survivorship. The prevalence of clinical levels of FCR (≥13) was evaluated by the Fear of Cancer Recurrence Inventory – Short Form (FCRI-SF) among non- and Hodgkin lymphoma survivors undergoing prior first-line chemotherapy. Among 108 lymphoma survivors with an average follow-up of 1.6 years (range 0.3–3.0 years), clinical levels of FCR (≥13) were observed for 44.4% (n = 48). Multivariate analysis indicated that baseline anxiety and low quality of life were related to clinically significant FCR levels.